Resistance hysteresis correlated with synchrotron radiation surface studies in atomic sp2 layers of carbon synthesized on ferroelectric (001) lead zirconate titanate in an ultrahigh vacuum. Issue 3 (8th January 2020) - Apostol, Nicoleta Georgiana; Lizzit, Daniel; Lungu, George Adrian; Lacovig, Paolo; Chirilă, Cristina Florentina; Pintilie, Lucian; Lizzit, Silvano; Teodorescu, Cristian Mihai
Abstract : Graphene-like layers synthesized in ultrahigh vacuum, characterized by surface science techniques, exhibit resistance hysteresis depending on the carbon coverage. Abstract : Carbon layers are deposited on 100 nm thick atomically clean (001) lead zirconate titanate (PZT) in ultrahigh vacuum, ruling out the presence of any contaminants. X-ray photoelectron spectroscopy is used to assess the substrate surface or interface composition, substrate polarization and the thickness of carbon layers, which ranges from less than one monolayer (1 ML) of graphene to several monolayers. Atomically clean PZT(001) exhibit inwards polarization, and this polarization reverses the sign upon carbon deposition. Cationic vacancies are detected near the PZT surface, consistent with heavy p doping of these films near the surface. The carbon layers exhibited a consistent proportion of atoms forming in-plane sp 2 bonds, as detected by near-edge absorption fine structure (NEXAFS) analysis and confirmed partially by scanning tunneling microscopy (STM). In situ poling with simultaneous in-plane transport measurements revealed the presence of resistance anti-hysteresis versus the polarization orientation for films with less than 1 ML carbon amount, evolving towards 'normal' hysteresis for thicker carbon films. The anti-hysteresis is explained in terms of a mixed screening mechanism, involving charge carriers from the sp 2 carbon layers together with holes or ionized acceptors in PZT(001) near the interface. For thicker films, the compensation mechanism becomes extrinsic, involving mostly electrons and holes from carbon, yielding the expected hysteresis.